Pelaksanaan Hak Jaminan Fidusia dalam Pemberian Kredit di Lembaga Perkreditan Desa di Desa Adat Mantring - Gede Bagus Andika Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
Fiduciary guarantees are promulgated through Article 5 paragraph (1) of Law no. 42 of 1999 which regulates movable or non-transferable commodities to become objects of collateral. According to Article 11 Paragraph (1), all commodities that will be charged with fiduciary security must be registered first, so that after being registered it is safe to issue a fiduciary guarantee deed. However, in the field application of fiduciary guarantees at the Mantring Traditional Village LPD, there are differences regarding its implementation with the contents of the Fiduciary Guarantee Law. The purpose of this research was to analyze the factors causing the non-registration of fiduciary guarantees at LPD Mantring and to discuss the efforts to settle what can be done by LPD Mantring in the case of debtors defaulting. This research is an empirical research, using a sociological approach. Sources of legal material are primary sources obtained from interviews with Mr. I Ketut Budiarta as chairman of LPD Mantring Tampaksiring and Mr. Made Sudiarsana as secretary at LPD Mantring Tampaksiring. The data collection techniques for this research are Observation Techniques and Interview Techniques. The results of the research explain that there is a reason why the LPD Mantring did not register the Fiduciary Guarantee agreement, namely the problem of the cost of making a fiduciary guarantee deed which costs a lot and the value of the loan and guarantee for the debtor is small. The efforts taken by the Mantring Traditional Village LPD to resolve the default case use 2 dispute resolution methods, namely dispute resolution can be reached through non-litigation and litigation.